Penerapan Metode Karya Wisata pada Pembelajaran Tematik Tema 1 Indahnya Kebersamaan Siswa Kelas IV MIS Mutiara Insan Palangkaraya - Anggi Renada (Al-Mudarris, 2019)
Background of the research was the lack of learning method use in study room particularly for fourth graders on thematic learning. The purposes of the research is for knowing of planning and implementing field tripmethod in thematic learning for class IV MIS Mutiara Insan Palangka Raya.The research used descriptive qualitative method with research subject a teacher of thematic learning/homeroom teacher class IV, headmaster, and two students MIS Mutiara Insan as informants. Research data were collected by observing,interviewing, and documenting. The research showed that: 1) The first plan teacher created was formulating the purpose of field trip, determining the appropriate lesson material for the method, determinelocation of field trip and object observed, provide students’ learning equipments, and divided students in five groups. 2) Implementation who did by teacher agree with the plan has done. Teacher delivered the purpose of field trip, teacher delivered material of social variety, economic, culture, ethnic and religion, teacher found students’ knowledge and experience, teacher guided and directed students during activity of field trip and students took note all they found and analyzed and students in group presented the report of field trip. 3) the following up of field trip method on thematic learning theme 1 the beauty of togetherness toward fourth graders MIS Mutiara Insan Palangka Raya students take note the result of finding that analyzed and discussed with friends in group then present the report of field trip front of class.